2011
DOI: 10.1007/s12013-011-9218-0
|View full text |Cite
|
Sign up to set email alerts
|

Down-Regulation of Tumor-Associated NADH Oxidase, tNOX (ENOX2), Enhances Capsaicin-Induced Inhibition of Gastric Cancer Cell Growth

Abstract: Gastric cancer is a common human malignancy and a major contributor to cancer-related deaths worldwide. Unfortunately, the prognosis of most gastric cancer patients is poor because they are generally diagnosed at a late stage after the cancer has already metastasized. Most current research, therefore, emphasizes selective targeting of cancer cells by apoptosis-inducing agents. One such therapeutic agent is capsaicin, a component of chili peppers that has been shown to possess anti-growth activity against vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 54 publications
4
40
0
1
Order By: Relevance
“…In pure mitochondria, inhibited mitochondrial complex-I and complex-III, but not in normal cells Tumors from mice fed orally 2.5 mg/kg capsaicin showed decreased SOD activity and increased ratio of oxidized glutathione to glutathione Wang et al 2011 Human SNU-1 and TMC-1 gastric normal cells. For instance, Richeux et al (1999) reported that cytotoxicty and DNA fragmentation was induced in human neuroblastoma SHSY-5Y cells by 25-100 mM capsaicin, with an IC 50 of 60 mM for the inhibition of protein synthesis.…”
Section: Direct Effects On Cancerous Cellsmentioning
confidence: 95%
“…In pure mitochondria, inhibited mitochondrial complex-I and complex-III, but not in normal cells Tumors from mice fed orally 2.5 mg/kg capsaicin showed decreased SOD activity and increased ratio of oxidized glutathione to glutathione Wang et al 2011 Human SNU-1 and TMC-1 gastric normal cells. For instance, Richeux et al (1999) reported that cytotoxicty and DNA fragmentation was induced in human neuroblastoma SHSY-5Y cells by 25-100 mM capsaicin, with an IC 50 of 60 mM for the inhibition of protein synthesis.…”
Section: Direct Effects On Cancerous Cellsmentioning
confidence: 95%
“…In fact, we previously discovered that capsaicin has divergent effects on the growth of gastric cancer cells that parallel its effects on tNOX expression, apoptosis in association with reduced tNOX expression in SNU-1 gastric cancer cells, and little apoptosis accompanied by insignificant changes in tNOX in the TMC-1 metastatic gastric carcinoma line. 4 However, whether the intracellular NAD + /NADH ratio also contributed to the different cellular responses between these two gastric cancer lines was not examined. Experiments utilizing tNOX-knockdown cells showed that tNOX-depletion decreased the intracellular NAD + /NADH ratio compared to that in control cells ( Figure 5), further confirming a regulatory role of tNOX in maintaining the NAD + /NADH redox status.…”
Section: Journal Of Agricultural and Food Chemistrymentioning
confidence: 99%
“…The molecular mechanisms underlying capsaicin-induced apoptosis are cell-type dependent. Despite the cumulative evidence for the tumor suppressive effects of capsaicin, few studies have been undertaken concerning the effects of capsaicin on cell signaling and molecular pathways leading to apoptosis in gastric cancer (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%